Faecalibacterium prausnitzii promotes intestinal epithelial IL-18 production through activation of the HIF1α pathway - Fagundes, Raphael R.; Bravo-Ruiseco, Gabriela; Hu, Shixian; Kierans, Sarah J.; Weersma, Rinse K.; Taylor, Cormac T.; Dijkstra, Gerard; Harmsen, Hermie J. M.; Faber, Klaas Nico (Frontiers in Microbiology, 2023)
Intestinal epithelial cells produce interleukin-18 (IL-18), a key factor in promoting epithelial barrier integrity. Here, we analyzed the potential role of gut bacteria and the hypoxia-inducible factor 1α (HIF1α) pathway in regulating mucosal IL18 expression in inflammatory bowel disease (IBD). Mucosal samples from patients with IBD (n=760) were analyzed for bacterial composition, IL18 levels and HIF1α pathway activation. Wild-type Caco-2 and CRISPR/Cas9-engineered Caco-2-HIF1A-null cells were cocultured with Faecalibacterium prausnitzii in a "Human oxygen-Bacteria anaerobic" in vitro system and analyzed by RNA sequencing. Mucosal IL18 mRNA levels correlated positively with the abundance of mucosal-associated butyrate-producing bacteria, in particular F. prausnitzii, and with HIF1α pathway activation in patients with IBD. HIF1α-mediated expression of IL18, either by a pharmacological agonist (dimethyloxallyl glycine) or F. prausnitzii, was abrogated in Caco-2-HIF1Anull cells. Butyrate-producing gut bacteria like F. prausnitzii regulate mucosal IL18 expression in a HIF1α-dependent manner that may aid in mucosal healing in IBD.